Upaya Pencegahan Anemia pada Populasi Dewasa melalui Penapisan Kadar Hemoglobin dan Hematokrit di Wilayah Kelurahan Grogol - Linda Julianti; Alexander Halim Santoso; Farell Christian Gunaidi; Harfi Rif’ani Apriansyah; Ayunda Vidya Karmelia BR Harahap (Lembaga Pengembangan Kinerja Dosen, 2025)
Anemia is one of the major health problems that often occurs in the adult population and has a major impact on quality of life, especially due to its risk of decreased immunity, productivity, dry skin, and increased risk of complications such as infection, cognitive impairment, and cardiovascular disease. Early symptoms of anemia are often not recognized, because complaints such as fatigue, dizziness, or pale and dry skin are often considered normal. The Community Service Program (PKM) implemented in Grogol Village aims to increase public awareness of the importance of early detection of anemia through hemoglobin and hematocrit screening activities. This activity uses the Plan-Do-Check-Act (PDCA) approach, which includes blood tests with Point-of-Care Testing (POCT) tools and education about symptoms, risk factors, and prevention of anemia. Of the 71 participants involved, 37 people (52.11%) were identified as having anemia, while 34 people (47.89%) had normal hemoglobin levels. These results indicate that early anemia screening is very important to prevent long-term complications and is the basis for building public awareness of the importance of maintaining optimal hemoglobin levels to support sustainable health and quality of life.